PENGARUH DILUSI TERHADAP VARIASI KADAR NIKEL (NI) PADA PROSES PENAMBANGAN NIKEL LATERIT DI PT X, SULAWESI TENGGARA - I Putu Benayaka Hananduta; Irfan Marwanza; Suliestyah (PT. Hasba Edukasi Mandiri, 2026)
Dilution is one of the main factors affecting nickel grade variation during lateritic nickel mining because it causes the mixing of ore with low-grade ore or waste material, resulting in a reduction in ore quality. This study aimed to analyze the effect of dilution on nickel (Ni) grade variation during the lateritic nickel mining process at PT X, Southeast Sulawesi, and to identify the operational factors contributing to dilution. A quantitative descriptive method with an ex post facto approach was employed by comparing nickel grades obtained from test pit sampling and stockpile re-sampling. A total of 20 test pit samples and 20 stockpile samples were analyzed using X-Ray Fluorescence (XRF). The results showed that the average nickel grade decreased from 1.427% Ni in the test pit to 1.377% Ni in the stockpile, with an average difference of 0.050% Ni, indicating that dilution occurred during the mining and material handling processes. Field observations revealed that relatively narrow mining faces, inadequate implementation and supervision of selective mining along the ore boundary, and water accumulation on the pit floor were the main operational factors contributing to dilution. The findings indicate that nickel grade variation is influenced not only by the characteristics of the ore deposit but also by the effectiveness of operational control during mining activities. Therefore, improving grade control practices and implementing more effective selective mining are essential to minimize dilution and maintain consistent nickel ore quality throughout the mining process.